Transnational Korean Television: Cultural Storytelling and Digital Audiences - Ju, Hyejung (Lexington Books, 2020)
Transnational Korean Television: Cultural Storytelling and Digital Audience provides previously absent analyses of Korean TV dramas' transnational influences, peculiar production features, distribution, and consumption to enrich the contextual understanding of Korean TV's transcultural mobility. Even as academic discussions about the Korean Wave have heated up, Korean television studies from transnational viewpoints often lack in-depth analysis and overlook the recently extended flow of Korean television beyond Asia. This book illustrates the ecology of Korean television along with the Korean Wave for the past two decades in order to showcase Korean TV dramas' international mobility and its constant expansion with the different Western television and their audiences. Korean TV dramas' mobility in crossing borders has been seen in both transnational and transcultural flows, and the book opens up the potential to observe the constant flow of Korean television content in new places, peoples, manners, and platforms around the world. Scholars of media studies, communication, cultural studies, and Asian studies will find this book especially useful.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television in Post-Reform China: Serial Dramas, Confucian Leadership and the Global Television Market - Zhu, Ying (Routledge, 2008)
This book explores the political, economic, and cultural forces, locally and globally that have shaped the evolution of Chinese primetime television dramas, and the way that these dramas in turn have actively engaged in the major intellectual and policy debates concerning the path, steps, and speed of China’s economic and political modernization during the post-Deng Xiaoping era. It intertwines the evolution of Chinese television drama particularly with the ascendance of the Chinese New Left that favors a recentralization of state authority and an alternative path towards China’s modernization and China’s current administration’s call for building a "harmonious society." Two types of serial drama are highlighted in this regard, the politically provocative dynasty drama and the culturally ambiguous domestic drama. The book also provides cross-cultural comparisons that parallel the textual and institutional strategies of transnational Chinese language TV dramas with dramas from the three leading centers of transnational television production, the US, Brazil and Mexico in Latin America, and the Korean-led East Asia region. The comparison reveals creative connections while it also explores how the emergence of a Chinese cultural-linguistic market, together with other cultural-linguistic markets, complicates the power dynamics of global cultural flows.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

The Television of Intervention: Mediating Patron–Client Ties in the Philippines - Corpus Ong, Jonathan (Television Histories in Asia: Issues and Contexts, 2015)
Similar to the other countries discussed in this volume, elite dominance over mass media has been a main characteristic of Filipino history. Foreign-educated Filipino intellectuals from wealthy families founded the early periodicals that demanded reform and/or independence from Spanish colonization in the late nineteenth century (Anderson 1983 ). Today, ‘old rich’ landowning families own and operate television networks, radio stations, and newspapers not only as part of prestigious and profi table media conglomerates, but also in connection with their interests in industries as varied as oil and agriculture to insurance, shipping, and mining.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Philippines (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Trust and Television in Globalizing India - McMillin, Divya (Television Histories in Asia: Issues and Contexts, 2015)
Writing a history of Indian television immediately begs the question, how do we want it read? Exhaustive chronological treatments anchor the field (Kumar 2000 ), ideological examinations reveal a Hindu-centric nation with serious consequences for religious and gender minorities (Rajagopal 1996 ; Mitra 1993 ; Van der Veer 1997 ), development analyses demonstrate the failures of a socialist state (F ü risch and Shrikhande 2007 ), and audience studies reveal complex negotiations among multiple identity positions (Mankekar 1999 ). These critical approaches to the study of television in India rightly expose power differentials that facilitate, through the centuries, the inequities of interwoven structures of imperialism, colonialism, casteism, and capitalist patriarchy. Most importantly, they highlight the chronic condition of distrust in postcolonial societies, making it highly challenging to legitimize profi table connections to global circuits as they modernize under the very conditions that once constrained them.
Num Pages: 20
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Continental Reality Television and the Expansion of South African Capital - Jacobs, Sean (The Politics of Reality Television: Global Perspectives, 2010)
This chapter wants to argue two things: the ﬁrst part suggests that reality television in Africa – speciﬁcally the series Big Brother Africa, which completed its third season in November 2008 – has had profound impacts for identity politics, gender politics, and the politics of class on the continent. In fact, these are the issues most commonly illuminated by reality television and I wrote about these in a previously published article. The second part of the chapter moves into less explored territory. In that previous article, I brieﬂy discussed how speciﬁcally Big Brother Africa can illuminate the workings of globalization in Africa and, in particular, South Africa’s hegemonic role in that process. Here, I expand on my earlier argument by exploring that hegemony in the context of the growing Chinese presence in Africa. All economic and political indicators suggest that China’s growing investment in mining and infrastructure and its political clout relative to South Africa mean that it is destined to assume a place of prominence on the continent. But here I want to argue that if we want to understand how globalization plays out in Africa, we need to look beyond China’s military and economic expansion. For me, Big Brother Africa can help us make sense of these dynamic processes. South Africa has consistently remained the highest-ranking country in Africain terms of its “global competitiveness” as measured by the World Economic Forum. South Africa dominates regional markets in Southern Africa as well as remaining competitive in the rest of the continent against business rivals from United States and Europe. As it was under Apartheid, there is a close symbiosis between the continental aspirations and interests of the postapartheid state and that of South African business. The advent of democracy in 1994 has opened up African markets for South African business on an unprecedented scale. The South African state is very active on the African continent and keen to develop a leading role for itself. In fact, successive United States governments have viewed South Africa as a continental leader. For example, former President George W. Bush referred to former South African President Thabo Mbeki as his “point man in Africa.”4The South African government underwrites and actively promotes SouthAfrican business’s continental schemes through its “Proudly South African” campaign coordinated through an International Marketing Council situated in the Oﬃce of (the country’s) President since 2002, which links state nationalism with consumption. Separately a statutory Industrial Development Corporation (established in 1940) underwrites the business expansion of South African capital.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Reality Television and the Making of Mobile Publics: The Case of Indian Idol - Punathambekar, Aswin (The Politics of Reality Television: Global Perspectives, 2010)
In the summer of 2007, media coverage of Indian Idol-3 focused attention on how people in the Northeast Indian state of Meghalaya cast aside decades-old separatist identities to mobilize support for Amit Paul, a ﬁnalist from the region. While some fans set up websites and blogs to generate interest and support from the rest of the country and abroad, others formed a fan club and facilitated eﬀorts by a range of groups and organizations to sponsor and manage PCOs (public call oﬃces) in diﬀerent parts of Meghalaya, distribute pre-paid mobile phone cards, and set up landline voting booths. Recognizing the ways in which these activities were beginning to transcend long-standing ethnic, religious, linguistic, and spatial boundaries, state legislators and other politicians soon joined the eﬀort to garner votes for Amit Paul, with the chief minister D. D. Lapang declaring Amit Paul to be Meghalaya’s “brand Ambassador for peace, communal harmony and excellence.”1 It seemed that this three-month-long campaign around a reality television program could set the stage for a remarkable refashioning of the socio-cultural and political terrain in Meghalaya. As one commentator remarked:When Meghalaya’s history is written, it could well be divided into two distinct phases – one before the third Indian Idol contest and one after it. A deep tribal-non-tribal divide, punctuated by killings, riots, and attempts at ethnic cleansing, would mark the ﬁrst phase. A return to harmony and to the cosmopolitan ethos of the past would signify the second. The agent of change: Amit Paul, the ﬁnalist of the musical talent hunt on a TV channel.
Num Pages: 21
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Big Brother, Bigg Boss: Reality Television as Global Form - Sen, Biswarup (Channeling Cultures: Television Studies from India, 2014)
This chapter looks at one well-known format in reality television– Big Brother (Bigg Boss in India) – in order to shed light on the complicated relationship between the forces of globalization, national and local cultural formations and the dictates of commercially driven entertainment. It analyses the essential features of format television to argue that the very mode of its constitution as an economic and aesthetic object inclines it towards the global. The chapter elucidates the reality behind global cultural formations by discussing the two main theoretical approaches to the question of global culture – cultural imperialism and cultural globalization. It also offers some speculations about how reality television embodies global form and thus functions as a sort of “Bigg Boss” that dictates contemporary modes of meaningful behaviour.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Spaces of Television: Rethinking the Public/Private Divide in Postcolonial India - Kumar, Shanti (Channeling Cultures: Television Studies from India, 2014)
This chapter critically evaluates changing definitions of ‘public’ in Indian television in relation to discourses of globalization and media privatization. It examines the debate over the nationalist agenda of public broadcasting in India in relation to the demands for alternative models of broadcasting, and the rise of private commercial satellite channels since the 1990s. It also discusses how representations of traditionally private desires of sexuality and intimacy in soap operas, reality TV shows and music television are redefining the public in India. It outlines the ways in which private desire is made visible — and thus made public — through the convergence of the television screen, the cinematic screen, the computer screen, and the mobile screen. It argues that binaries of ‘public’ versus ‘private’ force us into either/or debates even though such category systems are always-already hybrid in postcolonial societies such as India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television, Narrative Identity, and Social Imaginaries: Hermeneutic Approach - Asthana, Sanjay (Channeling Cultures: Television Studies from India, 2014)
The chapter argues that Paul Ricouer’s hermeneutics offers a way forward in examining not only the ideological and narrative structures of television, but also particular modalities through which viewers appropriate and interpret televisual texts. To this end, the chapter shall sketch an analytic framework by bringing together Ricoeur’s hermeneutic philosophy, particularly his concepts of narrative identity and temporality, and the notion of social imaginaries developed by postcolonial theory in a productive dialogue. Ricoeur’s hermeneutics presents an understanding of the human subject in terms of an embodied subjectivity that takes us beyond singular conceptions of identity, whether in terms of the abstract Cartesian subject, or various other discourse-centred theorizations of subject. The chapter demonstrates that the notion of embodied subjectivity and social imaginaries enable a better grasp in examining the articulations of class, caste, gender, and religious identities on Indian television.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Televisual Temporalities and the Affective Organization of Everyday Life - Mankekar, Purnima (Channeling Cultures: Television Studies from India, 2014)
This chapter sketches a theoretical framework for analyzing the role of television in the temporal and affective organization of everyday life. Rather than engage an empirical analysis of the “impact” of television, the chapter aims to raise conceptual questions about how satellite television participates in the creation of regimes of affect and temporality. Diverging from theories of transnational media that foreground the ubiquity of spatiality, it proposes that we examine how duree and histoire, historical consciousness and the everyday are co-constructed through the affectivity of television. The chapter begins by examining the work of television news in the production of crisis; it analyses how television enables the formation of historical consciousness; and it points to the ways in which television participates in the creation of a sense of the everyday. It thus outlines some of the ways that we can theorize the centrality of television to the production of temporalities of historicity, contemporaneity, and futurity.
Keywords: 1-TV; 2-Approches sociologiques; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

The Evolution of Black Women in Television: Mammies, Matriarchs and Mistresses - Cheers, Imani M. (Routledge, 2017)
This book seeks to interrogate the representation of Black women in television. Cheers explores how the increase of Black women in media ownership and creative executive roles (producers, showrunners, directors and writers) in the last 30 years affected the fundamental cultural shift in Black women’s representation on television, which in turn parallels the political, social, economic and cultural advancements of Black women in America from 1950 to 2016. She also examines Black women as a diverse television audience, discussing how they interact and respond to the constantly evolving television representation of their image and likeness, looking specifically at how social media is used as a tool of audience engagement.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Cultural Economy and Television in Jamaica and Ghana: #decolonization2point0 - Hickling Gordon, Deborah (Palgrave Pivot, 2020)
This book proposes contemporary decolonization as an approach to developing cultural economies in the Global South. This book represents the first critical examination and comparison of cultural and creative industries (CCI) and economy concepts in the Caribbean and Africa.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Ghana (corpus analysé); Jamaïque (corpus analysé); Jamaïque (lieu de production du savoir); _Nettoyé

Culturaly Refigured: Assimilating Oedipus Rex into the Yoruba Mythical Universe Through Television Adaptation Processes - Ige, Segun (Television in Africa in the Digital Age, 2021)
Colonisation bequeathed classical education, among others, to the African continent. The post-colonial utility, function and status of such a knowledge system have been questioned and resisted, and African knowledgebased institutions are making efforts to decolonise such systems. The decolonial project has also impacted popular culture in the sense that African identity and self-presentation are being interrogated using various methods. Adaptations and productions of classical myths are implicated in this discourse. Implicated adaptations serve as platforms for allegorical cross-cultural conversation on shared experiences of a people group, perhaps of an earlier generation with the assumption of partial or absolute continuities. Continuity discourse is problematic when two cultures are implicated, particularly, when one is a colonial culture and the other colonised. The unity of discourse is either afﬁrmed, violated or reconstituted.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (lieu de production du savoir)

Pimpin' Ain't Easy: Selling Black Entertainment Television - Smith-Shomade, Beretta E. (Routledge, 2007)
Launched in 1980, cable network Black Entertainment Television (BET) has helped make blackness visible and profitable at levels never seen prior in the TV industry. In 2000, BET was sold by founder Robert L. Johnson, a former cable lobbyist, to media giant Viacom for 2.33 billion dollars. This book explores the legacy of BET: what the network has provided to the larger US television economy, and, more specifically, to its target African-American demographic. The book examines whether the company has fulfilled its stated goals and implied obligation to African-American communities. Has it changed the way African-Americans see themselves and the way others see them? Does the financial success of the network - secured in large part via the proliferation of images deemed offensive and problematic by many black communities - come at the expense of its African-American audience? This book fills a major gap in black television scholarship and should find a sizeable audience in both media studies and African-American studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Brown Girls Who don’t Need Saving: Social Media and the Role of ‘Possessive Investment’ in The Mindy Project and The Good Wife - Moorti, Sujata (Television for Women, 2016)
This poignant assertionby acclaimed actor Viola Davis, star of the series How to GetAway with Murder (ABC, 2014-), during her Emmy acceptance speechwent viral and becamethe flashpoint for heated discussion about contemporary television’s representational practices. The statement draws attention to questions of taste, what is acknowledgedby the industry and audiences as quality television and the political economy of thecontemporary industry. This moment in television history, with its attendant socialmedia afterlife, captures the key elements I wish to explore in this chapter: represen-tations of women of colour, production practices and viewer responses. As Viola Davisnotes in the quote above, the contemporary US television landscape offers limited rolesfor people of colour. The few shows starring people of colour have become the focus ofintense social media exchanges. In this chapter, I will explore how televisual womenof colour have become a key site from which viewers assert a possessive investmentof racialised identity. By focusing on social media responses, I delineate the ways inwhich viewers invest symbolic and literal ownership over these representations.Through such a multifaceted examination, this essay aims to elaborate how women ofcolour are accommodated within the concept of television for women, a term inter-rogated in this volume. In addition, I illustrate the ideological instability of the term‘women of colour’ and the capaciousness of the concept ‘television for women’.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Shaded Lives: African-American Women and Television - Smith-Shomade, Beretta E. (Rutgers University Press, 2002)
Since its invention, television has been one of the biggest influences on American culture. Through this medium, multiple visions and disparate voices have attempted to stake a place in viewer consumption. Yet even as this programming supposedly reflects characteristics of the general American populace, television-generated images are manipulated and contradictory, predicated by the various economic, political, and cultural forces placed upon it. In Shaded Lives, Beretta Smith-Shomade sets out to dissect images of the African American woman in television from the 1980s. She calls their depiction "binaristic," or split. African American women, although an essential part of television programming today, are still presented as distorted and deviant. By closely examining the television texts of African-American women in comedy, music video, television news and talk shows (Oprah Winfrey is highlighted), Smith-Shomade shows how these voices are represented, what forces may be at work in influencing these images, and what alternate ways of viewing might be available. Smith-Shomade offers critical examples of where the sexist and racist legacy of this country collide with the cultural strength of Black women in visual and real-lived culture. As the nation's climate of heightened racial divisiveness continues to relegate the representation of Black women to depravity and display, her study is not only useful, it is critical.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Romance in Post-Socialist Chinese Television - Wen, Huike (Palgrave Macmillan, 2020)
"Surveying the latest Chinese TV shows centered on romantic relationships, this book joins the expanding body of literature on the ever-evolving structures of feelings while breaking new grounds in media studies. With its thorough investigation of a wide range of genres, narratives, and public discourses, the volume makes timely and significant contributions to the fields of media studies, China studies, and the cultural history of love and romance."–Hui Faye Xiao, University of Kansas, USA "What does romantic love mean for Chinese people today? How is love represented in popular Chinese television programs? Huike Wens fascinating and important book explores how romantic love promises young Chinese urbanites individual freedom, fulfillment, and purpose in life, yet also plays an ideological role in creating social cohesion and maintaining traditional patriarchal values in post-socialist China. An entertaining and thought-provoking insight into how love functions in contemporary Chinese society." –Hsu-Ming Teo, Macquarie University, Australia This book examines how representations of romantic love in Chinese television programs reflect the contradictions inherent to changing dominant values in post-socialist Chinese mainstream culture. These representations celebrate individual freedom, passion, and gender equality, and promise change based on individual diligence and talent, while simultaneously obstructing the fulfillment of these ideals. Huike Wen is an Associate Professor at Willamette University (Salem, Oregon). Her research focuses on the intersection of genders, emotions, media technology, and nations in transnational Chinese and East Asian media and culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television and the Modernization Ideal in 1980s China: Dazzling the Eyes - Wen, Huike (Lexington Books, 2013)
Television and the Modernization Ideal in 1980s China: Dazzling the Eyes explores Chinese television history in the pivotal decade of the 1980s and explains the intellectual reception of television in China during this time. While the Chinese media has often been a topic within studies of globalization and the global political economy, scholarly attention to the history of Chinese television requires a more extensive and critical view of the interaction between television and culture. Using theories of media technology, globalization, and gender studies supplemented by Chinese periodicals including Life Out of 8 Hours, Popular TV, Popular Cinema, Modern Family, and Chinese Advertising, as well as oral history interviews, this book re-examines how Western technology was introduced to and embedded into Chinese culture. Wen compares and analyzes television dramas produced in China and imported from other nations while examining the interaction between various ideologies of Chinese society and those of the international media. Moreover, she explores how the hybridity between Western television culture and Chinese traditions were represented in popular Chinese visual media, specifically the confusions and ambitions of modernization and the negotiation between tradition and modernity, nationalism and internationalism, in the intellectual reception of television in China.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Real Housewives or Real Lies? New Constructions of "Housewives" on The Real Housewives of Atlanta - Shorter, Shavonne R. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
An old adage prescribed that “art imitates life.” If one believes this to be true, then it is plausible that entertainment is a source from which information about everyday life can be gleaned? Can U.S. television shows provide a looking glass into how Americans perform certain aspects of their lives? For a “real” look into how careers are performed, I have examined content from a reality television show which bears a title that implies something about the cast— the Bravo Network’s Real Housewives of Atlanta series. This show was chosen for two reasons. First, The Real Housewives of Atlanta is the most popular show among the “Housewives” franchise. Thus with each airing of the show, those who watch have the opportunity to learn more about the career aspirations, roles, and behaviors, of the cast members. Second, this is the only show within The Real Housewives franchise that features a primarily black cast. As such, the question emerges— can this show provide insight into the way black women construct their career roles? Another goal of this study is to determine how cast members construct notions of housewifery. Hence, throughout this chapter, readers will see that these women are not the typical “housewives,” rather they have reinvented what it means to be a housewife in the modern age.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The "Down Ass Bitch" in the Reality Television Show Love and Hip Hop: The Image of the Enduring Black Women and Her Unwavering Support of the Black Man - Alameen-Shavers, Antwanisha (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Within Spoken Soul, better known as Ebonics, the term down can be used as an adjective to describe a person that willingly yields a tremendous amount of support to another person. The “Down Ass Bitch” (DAB) is a controlling image of the black woman that calls for her unwavering support of the black man, even when it is pernicious to her best interest. In fact, we can see this in the black community on many levels: (1) from black women faithfully waiting years for men to be released from prison; (2) hiding domestic abuse or rape at the hands of black men for the sake of protecting the race; or (3) sexually exploiting our bodies for the financial benefit of black men. However, what is most interesting about this particular stereotype of the black woman being “down” for her man is that this is not an expectation that is asked of the black man. It is this author’s contention that the “Down Ass Bitch” is obsequious to the powers of black men— though she is portrayed as being strong, aggressive, and assertive. Essentially, the “Down Ass Bitch,” a highly celebrated image in the black community, is the black version of the submissive white woman, the Eurocentric construction of the idealized womanhood. Various controlling images of black womanhood— such as the mammy, the jezebel, and the welfare queen— served as justifications for the oppression of black women and have been discussed significantly by scholars.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Dehumanized and Empowered? Black Women, Reality Television, and Love and Hip Hop Atlanta - Bennett, Patrick; Griffin, Rachel Alicia (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
In recent years, scripted television has been joined by a more “realistic” look into peoples’ lives— reality television. Reality television claims to give viewers an unmediated glimpse into how real people live. The “realness” of reality television invokes controversy by providing a voyeuristic and potentially exploitive look into people’s lives. As the genre has matured, shows that offer insight into communities that are systemically underrepresented have become common. Indicative of this trend are shows that depict the lives of African Americans and opportunistically exploit representations of black culture for drama, ratings, and profit. One network that has taken considerable advantage of this is VH1— first, with the success of Flavor of Love and its spinoffs, then more recently with shows such as Basketball Wives and Love and Hip Hop. In fact, the excessive amount of fighting among Black women on Basketball Wives led to a boycott of the show, which prompted creator Shaunie O’Neal to promise less violence in its next season. Akin to Basketball Wives , Love and Hip Hop Atlanta exemplifies the trend of exploiting black culture. As members of the black community, we find ourselves both intrigued and troubled by the implications of the show. Capturing the essence of our paradoxical interpretation of Love and Hip Hop Atlanta — as one of many reality television shows that simultaneously reproduces and challenges negative stereotypes about blackness— are contradictory headlines such as “The 21 Most Ratchet Women of Black Reality TV,” “How Reality TV has Changed our Daughters,” and “Wealthy Reality Stars Humanize Black Women.”
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

A Critical Analysis of Black Womahood in NBC's The Apprentice - Griffin Padget, Donyale R.; Allison, Donnetrice C. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Reality programs rose to prominence based on claims that the shows depicted “real life,” but in recent years many shows have come under fire for being anything but “reality.” Orbe (1998) suggests viewers are drawn to such programs based on the notion that they show “real people in everyday interactions,” and there is a certain level of “unpredictability that comes with reality.” However, what has become predictable and potentially problematic, over the past two decades, are the negative stereotypes associated with African American women on these programs. This skewing of reality is particularly significant when we consider the limited opportunities these shows provide viewers to witness the many facets of black womanhood. From the head-bobbing and finger-waving of Alicia Calaway on season two of the hit show Survivor to the on-and-off-air mudslinging between Kenya Moore and NeNe Leakes of Real Housewives of Atlanta fame, black women are portrayed as disloyal, bitchy, lazy, difficult to work with, and a threat to others.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The "Tyra Tyrade": Reinforcing the Sapphire Through Online Parody - Patton, Tracey Owens; Snyder-Yuly, Julie (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Tyra Banks, supermodel and producer, is the creator of the reality show America’s Next Top Model ( ANTM ), which is now in its twenty-second cycle, and features contestants who present themselves to a panel of judges for modeling critique. ANTM has been nominated for twenty-nine awards, including the GLAAD Media Award and Image Award, and the show has received five awards in 2009 from the Teen Choice Award and the Director’s Guild of America Award. Further, ANTM is currently shown in over 120 countries. The winner of each cycle receives a featured spread in a magazine, a modeling contract with a prominent agency, and a $100,000 modeling contract from a cosmetics company. In 2005, however, there was an infamous episode— dubbed the “Tyra Tyrade,” —where Tyra Banks yelled at a contestant whom she had just eliminated from the show. This episode was parodied more than any other ANTM episode, with the penultimate parody shown on a 2007 episode of Family Guy (a primetime cartoon television show with millions of viewers each week), where Tyra turns into a lizard and eats the model. While this episode is now nine years old, parodies from as recently as 2014 continue to live on and, as we argue, perpetuate negative stereotypes of black womanhood, particularly as related to the Sapphire mediated stereotype— loud, bossy, angry black woman. From the various interpretations of the “Tyra Tyrade,” it is clear that those who created the parodies covertly and overtly ventured into maintaining white supremacist stereotypes of black womanhood— where one is supposed to be beautiful, a jezebel, or a mammy, but not a Sapphire. Continuing the marginalizing mediated tradition, in almost every parody, the Tyra character becomes the object of ridicule for being “excessively black” and outside the parameters of her hegemonically prescribed role, because she demonstrated negative emotions resulting in an assertion of her power as the expert.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Is She Strong or Just a B!@*#? Discussion of Black Women's Anger in the Reality Show Bad Girls Club - Goldman, Adria Y. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
It is near impossible to have a discussion of black women in reality television without mentioning the infamous Angry Black Woman (ABW). In fact, some critiques have argued reality television is damaging for black women since many shows focus heavily on this character. 1 This stereotypical characterization of black women is long-standing, due largely to its constant inclusion in media messages. As noted in chapter one, audiences were first officially introduced to her in the 1920s as Sapphire Stevens from the Amos ‘n’ Andy Show ; and her character continued to resurface throughout the years, across several different genres. Despite the many time periods through which this image has traveled, the key characteristic of the Sapphire— her unexplainable anger and aggression— seem to resonate in many modern day images of black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Can't Have It All: An Analysis of Black Motherhood on Reality Television - Alford, Allison M.; Maxwell, Madeline M.; Jones, Ryessia D.; Morris, Angelica N. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
In this chapter we analyze three reality TV (RTV) shows whose main characters do not fit the old movie stereotypes of dark-skinned maternal Mammies, bossy, brown Sapphires or light-skinned sexy Jezebels. Many RTV shows with black cast members are falling back on such stereotypical representations. In contrast, the female characters we analyze are smart and sophisticated, and they live in multi-racial environments. Hence, the primary mediarelated question we address concerns how one slice of black motherhood is represented. The social question we address concerns the extent to which the character presentations actually point to social progress, with diverse symbols and meaning making of real life, or are they as artificial and stereotypical— perhaps in new ways— as the old portrayals?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Are Black Women Loud? Neoliberal and Postfeminist Protagonists in OWN's Televisual Sphere - Briceño, Mia E.; Estwick, Evene (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Jones’ comments reflect a general consensus among TV critics and viewers that: 1) the black women who command the most attention on reality television tend to portray stereotypical, Sapphire-like characters; 2) as audiences consume such portrayals, there is a consistent line of argument from producers that insists “pitting [black women] against each other” is expected or “what the people want;” and 3) black female reality TV stars are willing to indulge the Sapphire fantasy if it means they will be able to further a personal and/or professional agenda. These are important themes to interrogate, especially given the history of mass mediated representations of black Americans, as well as the present-day “evolution” of black characters and other characters of color on unscripted and scripted American television. However, because attention is primarily focused on arguably “negative” portrayals, there has not been much critical analysis of “alternative” or more nuanced portrayals of black women in the televisual sphere. This chapter represents an attempt to fill in some of that blank space by focusing attention on an underexplored and relatively new consortium of reality television programming that features black women who are defined by their roles as mothers and entrepreneurs.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

From 1990s Girl to Hip-Hop Wife: An Analysis of the Portrayal of Tiny as Black Mother in Reality Television - Jones, Ryessia D.; Jones, Johnny; Smith, Siobhan E. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Although African-American women are still underrepresented in narrative television, reality television appears to be a site where one can find many portrayals of them. As other scholars have explained, the representations of African American women in reality television are usually negative, generally presenting them as loud, angry, and without “class.” However, there has been little research on the complicated relationships of black motherhood, black wifehood, and their portrayals on reality television. One black mother who illustrates this tense interaction is Tameka “Tiny” Harris, nee Cottle, formerly of the 1990s girl group Xscape, and star of two reality television programs— BET’s Tiny & Toya , and VH1’s T.I. and Tiny: The Family Hustle . Though both programs prominently feature Cottle, BET’s program constructs Tiny as an emotionally strong and pragmatically capable business woman who maintains the emotional health and financial stability of her family while her relational partner/husband, rapper Tip “T.I.” Harris, is serving time in prison. However, upon T.I.’s return home, The Family Hustle presents Tiny as having little business savvy and as overly permissive with their blended family. This is a dangerous portrayal, given that reality TV purports to disseminate some version of “reality” to its viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Queering/Quaring Blackness in Noah’s Arc - Yep, Gust A.; Elia, John P. (Queer Popular Culture: Literature, Media, Film, and Television, 2007)
This chapter provides a description and critical analysis of Noah’s Arc , a Logo cable television series featuring a predominantly African American gay male cast. Queer theory and quare studies are used as theoretical tools to examine the conceptions of blackness in general, as well as representations of blackness in Noah’s Arc . Thereafter this chapter turns to an analysis of the representations in this series to illustrate how Noah’s Arc not only queers and quares notions of authentic blackness but also serves to expand various notions of blackness. Finally, this chapter provides a treatment of how whiteness and heteronormativity are implicated in this recent iteration of a racialized queer visibility in popular culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The A to Z of African-American Television - Fearn-Banks, Kathleen (Scarecrow Press, 2009)
From Amos 'n' Andy to The Jeffersons to Family Matters to Chappelle's Show, this volume covers it all with entries on all different genres_animation, documentaries, sitcoms, sports, talk shows, and variety shows_and performers such as Muhammad Ali, Louis Armstrong, Bill Cosby, and Oprah Winfrey. Additionally, information can be found on general issues, ranging from African American audiences and stereotypes through the related networks and organizations. This book has hundreds of cross-referenced entries, from A to Z, in the dictionary and a list of acronyms with their corresponding definitions. The extensive chronology shows who did what and when and the introduction traces the often difficult circumstances African American performers faced compared to the more satisfactory present situation. Finally, the bibliography is useful to those readers who want to know more about specific topics or persons.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Pretty Liar: Television, Language, and Gender in Wartime Lebanon - Khazaal, Natalie (Syracuse University Press, 2018)
"Pretty Liar" explores the rise of language and gender politics on Lebanese television to tell the untold story of the co-evolution of Lebanese television and its audiences and how the civil war of 1975-1991 affected that co-evolution. The shift in public interest in television has been widely acknowledged and interpreted within an institutional context as a victory of the neo-liberal entrepreneurship of a new, agile brand over the government inefficiency of Lebanon's national station, Télé Liban. Yet, the role of the Lebanese Civil War in reshaping national television and broadcasting in Arab media following the emergence of the Lebanese Broadcasting Company in 1985 has been unexplored. Based on empirical data and grounded in theory by Arab and global researchers, "Pretty Liar" offers textual analyses of five Lebanese fictional series, three major and several additional periodicals, and nine literary works, and provides context from unscripted interviews with television administrators, anchors, actors, and freelance contributors, print journalists, and audience members. Khazaal seeks to offer new insight into how entertainment television became a site for politics and political resistance, feminism, and the cradle for post-war Lebanon due to the shift in practices and standards of legitimacy. The history of television in Lebanon is not merely the history of technology and business, Khazaal argues, but rather the history of a people and their continuing quest for a responsive television even during times of civil unrest.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Liban (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Muy buenas noches: Mexico, Television, and the Cold War - Gonzalez de Bustamante, Celeste (Nebraska Paperback, 2013)
By the end of the twentieth century, Mexican multimedia conglomerate Televisa stood as one of the most powerful media companies in the world. Most scholars have concluded that the company’s success was owed in large part to its executives who walked in lockstep with the government and the Partido Revolucionario Institucional (PRI), which ruled for seventy-one years. At the same time, government decisions regulating communications infrastructure aided the development of the television industry. In one of the first books to be published in English on Mexican television, Celeste González de Bustamante argues that despite the cozy relationship between media moguls and the PRI, these connections should not be viewed as static and without friction. Through an examination of early television news programs, this book reveals the tensions that existed between what the PRI and government officials wanted to be reported and what was actually reported and how. Further, despite the increasing influence of television on society, viewers did not always accept or agree with what they saw on the air. Television news programming played an integral role in creating a sense of lo mexicano (that which is Mexican) at a time of tremendous political, social, and cultural change. At its core the book grapples with questions about the limits of cultural hegemony at the height of the PRI and the cold war.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

South African Soapies: A “Rainbow Nation” Realized? - Burton, Nsenga K. (Watching While Black, 2012)
In the United States, daytime soap operas are often critiqued as escapist fantasies with narratives that provide leisure and pleasure for middle-class and stay-at-home mothers. The storylines typically involve forbidden sexual liaisons and business relationships, with physical and psychological behaviors that center on powerful families. One family unit usually represents “old money” while the other family represents “new money” or an upwardly mobile group with aspirations of power, status, and influence. The economic differences are usually the source of conflict between the families, around which all other social relationships develop. The temporal space expands and contracts to accommodate storylines, which
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Resistance Televised: The TV da Gente Television Network and Brazilian Racial Politics - Gillam, Reighan Alexandra (Watching While Black, 2012)
As activists and political leaders in Brazil call for increasing rights, recognition, and redress to address the multiple forms of marginalization that Afro-Brazilians have endured, media has become an increasingly important sphere through which different constituencies mobilize to advance a project of racial equality. Among these groups enlisting available media resources was a group composed predominately of Afro-Brazilian media professionals who joined together to launch the TV da Gente (Our TV) television network, Brazil’s first television station with the mission to produce racially diverse programming directed toward a Black viewing audience.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Graphic Blackness/Anime Noir: Aaron McGruder’s the Boondocks and the Adult Swim - Whaley, Deborah Elizabeth (Watching While Black, 2012)
Aaron McGruder’s “The Return of the King” (2006) is one of many of the artist’s controversial episodes, yet it stands out because of the criticism it received among mainstream media outlets and civil rights leaders. It was the ninth episode to air from his series The Boondocks, which is an anime show that airs on the Cartoon Network’s Adult Swim cable channel. McGruder presents the following scenario in “The Return of the King”: What if Martin Luther King Jr. (MLK) did not die after his April 4, 1968, shooting and instead awoke after being in a coma for thirty-two years?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Nigger, Coon, Boy, Punk, Homo, Faggot, Black Man: Reconsidering Established Interpretations of Masculinity, Race, ans Sexuality Through Noah’s Arc - Cunningham, Mark D. (Watching While Black, 2012)
At best, our knowledge about the lives and experiences of Black gay men is limited to a series of stereotypes, snap judgments, and ridicule. In terms of television media product, this aforementioned knowledge has been packaged mostly within the framework of comedy: a red-leather-clad Eddie Murphy talking about the most effective ways to shield his ass from the gay male gaze in the 1983 HBO stand-up performance Delirious ; Damon Wayans and David Alan Grier’s effeminate film critics Blaine Edwards and Antoine Merriweather on the 1990s television variety show In Living Color ; fashionista panel members Miss J and Andre Leon Talley
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Prioritized: The Hip Hop (Re)Construction of Black Womanhood in Girlfriends and the Game - Lewis, Nghana (Watching While Black, 2012)
Why is it important that a Black woman created, wrote for, and co-produced¹ two highly-regarded television situation comedies that engaged a variety of Black women’s health issues while at the same time these issues were being reduced, simplified, or altogether ignored in mainstream American hip hop? Mara Brock Akil tacitly responded to this question when asked why four episodes of the third season of Girlfriends (2000–2008), the situation comedy she created and co-produced for UPN, addressed the HIV/AIDS crisis among Black women in America. “I have things I want to say,” explained Brock Akil, “about bridging television’s gap between
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Keepin’ It Reality Television - Gates, Racquel (Watching While Black, 2012)
On November 4, 2008, CNN anchor Anderson Cooper appeared on The Ellen DeGeneres Show via satellite. One of the more memorable moments of the interview came when Cooper expressed shock that DeGeneres was unfamiliar with the hit Bravo television show The Real Housewives of Atlanta. “You mean you don’t know about NeNe?” he demanded incredulously, referring to cast member NeNe Leakes—the most outspoken and self-proclaimed “realest” of the Housewives. Cooper’s segment, along with his admission that Leakes was his favorite of the cast, brought even more attention to the already widely debated show, the first of Bravo’s Housewives series
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

“Hey, Hey, Hey!”: Bill Cosby’s Fat Albert as Psychodynamic Postmodern Play - Russworm, TreaAndrea M. (Watching While Black, 2012)
Although the cartoon series Fat Albert and the Cosby Kids (CBS, 1972–1984) averaged only nine new episodes a year during its twelve-year run (compared to a more standard production cycle of twenty-five to sixty new episodes a year for other cartoons), the show remained a highly popular option for young viewers on late Saturday mornings. By the time of the series’ network premiere in 1972, the cartoon’s animated African American stars—Weird Harold, Dumb Donald, Fat Albert, Rudy, Mushmouth, Bucky, Russell, and Bill—were familiar and recognizable to American audiences as originating from Bill Cosby’s boyhood community of North
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Blacks in the Future: Braving the Frontier of the Web Series - Acham, Christine (Watching While Black, 2012)
Television’s synergy with the Web initially seemed inconceivable to network executives. With the rise of Internet use, newspaper and magazine articles announced the impending death of television. While that was clearly hyperbole, network executives, though often anonymously, expressed their fears that Web content would siphon off viewership and thus advertising dollars generated by television programming. Fears may have been quelled with the evidence of the success of television shows first made available streaming on network websites and then for paid download through digital servers such as iTunes.
Keywords: 1-TV; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

A Black Cast Doesn’t Make a Black Show: City of Angels and the Plausible Deniability of Color-Blindness - Warner, Kristen J. (Watching While Black, 2012)
In a recent debate over the problematic characterization of Bonnie Bennett, the only Black female recurring character on the CW network series The Vampire Diaries (CW 2009), my challenger insisted that with all of the qualifiers I insisted she have, “maybe this is another hidden reason there are no minorities on television: everything becomes an issue and you just can’t win.” Indeed, the main qualifier I suggested that the series allow the character to possess—an innate sense of cultural difference—is difficult to grasp and maintain. However, I do not accept that just because race is difficult, it is
Keywords: 1-TV; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Two Different Worlds: Television as a Producer’s Medium - Coleman, Robin R. Means; Cavalcante, Andre M. (Watching While Black, 2012)
Although discourses regarding 1980s representations of Blackness on television heavily focus on The Cosby Show, its NBC spin-off series, A Different World, depicting student life at a historically Black college, was equally groundbreaking and deserving of critical attention. Looking to transfer the appeal and audience share of The Cosby Show to A Different World, the spin-off show’s first season centered on the life of The Cosby Show’s star Denise Huxtable (Lisa Bonet) at Hillman College. A Different World’s story provides an illuminating case study of the role and power of television producers, highlighting their influence over a show’s narrative and
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé)

Gandhi Meets Primetime: Globalization and Nationalism in Indian Television - Kumar, Shanti (University of Illinois Press, 2005)
Shanti Kumar's Gandhi Meets Primetime examines how cultural imaginations of national identity have been transformed by the rapid growth of satellite and cable television in postcolonial India. To evaluate the growing influence of foreign and domestic satellite and cable channels since 1991, the book considers a wide range of materials including contemporary television programming, historical archives, legal documents, policy statements, academic writings and journalistic accounts. Kumar argues that India's hybrid national identity is manifested in the discourses found in this variety of empirical sources. He deconstructs representations of Mahatma Gandhi as the Father of the Nation on the state-sponsored network Doordarshan and those found on Rupert Murdoch's STAR TV network. The book closely analyzes print advertisements to trace the changing status of the television set as a cultural commodity in postcolonial India and examines publicity brochures, promotional materials and programming schedules of Indian-language networks to outline the role of vernacular media in the discourse of electronic capitalism. The empirical evidence is illuminated by theoretical analyses that combine diverse approaches such as cultural studies, poststructuralism and postcolonial criticism.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Politics After Television: Hindu Nationalism and the Reshaping of the Public in India - Rajagopal, Arvind (Cambridge University Press, 2001)
In January 1987, the Indian state-run television began broadcasting a Hindu epic in serial form, The Ramayana, to nationwide audiences, violating a decades-old taboo on religious partisanship. What resulted was the largest political campaign in post-independence times, around the symbol of Lord Ram, led by Hindu nationalists. The complexion of Indian politics was irrevocably changed thereafter. In this book, Arvind Rajagopal analyses this extraordinary series of events. While audiences may have thought they were harking back to an epic golden age, Hindu nationalist leaders were embracing the prospects of neoliberalism and globalisation. Television was the device that hinged these movements together, symbolising the new possibilities of politics, at once more inclusive and authoritarian. Simultaneously, this study examines how the larger historical context was woven into and changed the character of Hindu nationalism.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Manufacturing the Gang: Mexican American Youth Gangs on Local Television News - Tovares, Raul Damacio (Greenwood Publishing Group, Incorporated, 2002)
Coverage of Mexican-American youth gangs has been a staple of local television news in the United States for decades, and its form and content have come to embody many journalistic cliches: the rising tide of violence, the spread of drug addiction, the alienated minority youth. But as this bold new study argues, these stories contain gross exaggerations that lead to the reinforcement of stereotypes about Mexican-American young people and the Mexican-American community in general. Indeed, the police and community leaders greatly influence the content of this coverage by deciding what information to make available to the news media, while reporters select certain sources and ignore others, thus slanting the story even further. Source: Publisher
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; États-Unis (lieu de production du savoir)

TV China: Control and Expansion - Zhu, Ying (The Routledge Companion to Global Television, 2019)
The chapter traces the evolution of Chinese television since 1958 from a state propaganda organ to a profit-generating media juggernaut, with China Central Television (CCTV) as the only network TV responding to both market principles and party directives. Commercialization and marketization played a major role in the rapid development of the Chinese television industry. In recent years China’s TV industry has witnessed the rise of private media companies and the rapid expansion of digital media and the proliferation of over the top (OTT) content. The chapter further provides an overview of China’s overall TV structures and teases out the relationship between CCTV and local stations. The most popular genre on Chinese TV is serial drama, which developed from predominantly single-episode anthology dramas in the 1980s to chiefly multi-episode serial dramas. Talk shows and reality TV became fashionable since the late 1990s.
Num Pages: 9
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Chine (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé; États-Unis (lieu de production du savoir)

Refashioning Chinese Television Through Digital Fun - Bai, Ruoyun (The Routledge Companion to Global Television, 2019)
This chapter discusses how Chinese television has been refashioned by the digital entertainment industry, and contends that new genres, identities, and representations have emerged in recognition of youths as the most valuable and desirable category of audience. It does so by way of three case studies. The first illustrates the symbiotic relationship between online literature and television drama production, and how the former contributes to the fantastical turn of Chinese television. The second seeks to understand the emergence of new cultural figures of “supreme heroine” and “sweet males” in the context of the rise of female fandom in contemporary Chinese popular culture. The third reveals how traditional television content, or in this case a political drama, may be recreated by online distributors and influencers so as to be aligned with the habits, attitudes, and preferences of the younger audiences. The chapter concludes that to understand contemporary Chinese television culture, the Internet and social media must become an integral component of inquiry because of their powerful remediating role in the public communication of any cultural text.
Num Pages: 12
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Identités diasporiques; Canada (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Idol Worship: Ethnicity and Difference in Global Television - Sen, Biswarup (Global Television Formats: Understanding Television Across Borders, 2012)
The worldwide success of the Idol format may not require any explanation. We live under the ubiquitous sign of globalization; and hence it should come as no surprise that mass media— which together constitute an ecumenical vehicle of culture with an insatiable appetite for proﬁt— would generate forms (or formats) of art that travel with ease and are translatable into every context. The reception of these formats is, at one level, as unproblematic as its dissemination. To be global (and who isn’t?) is to be eagerly accepting of certain languages, technologies, discourses and styles. The craze surrounding competitive singing can then be explained as one more instance of borders proving permeable to the formulas of international popular culture. It is my argument that in order to understand the unique valence and signiﬁcance of global formats, we need to go beyond issues of production, distribution and reception, and focus instead on the phenomena that arise from their instantiation . This is so because implementing a format in a speciﬁc context has consequences that are neither written into the “program” nor purely derivable from local conditions. Let me provide an illustration. The call-in talk show has recently become a staple on Indian television. The format and content of these shows would be familiar to most Western viewers— a regular host, one or more “experts” discussing politics and culture, and a ﬁnal segment devoted to phone calls from the public.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Asie du sud (corpus analysé); Inde (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

More than Copycat Television: Format Adaptation as Performance - Navarro, Vinicius (Global Television Formats: Understanding Television Across Borders, 2012)
As a trend that captured the imagination of Brazilian audiences, the rapid proliferation of dance competitions on network television is meaningful not simply as a domestic phenomenon but also, and particularly, as an illustration of the mechanisms that enable the global popularity of formatted programs. While the shows were locally produced and relied on local talent, they were all based on formats that originated elsewhere, “imported ideas” that were recycled by Brazilian producers. References to foreign versions of the formats were also part of the discourses through which the domestic adaptations were described. As one show followed the other, they invited comparisons not only among themselves but also with their international counterparts. Yet, despite the association with foreign TV shows, the formats were easily incorporated to Brazil’s television culture, a feat that could surprise neither critics nor the industry.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Interpreting Cubanness, Americanness, and the Sitcom: WPBT-PBS’s ¿Qué pasa U.S.A.? (1975–1980) - Rivero, Yeidy M. (Global Television Formats: Understanding Television Across Borders, 2012)
I was about 10 or 11 years old when I, together with my parents, religiously tuned in weekly to the situation comedy ¿Qué pasa U.S.A.? While I do not recall the speciﬁc year the show aired in Puerto Rico, I do remember that it was broadcast on WIPR-Channel 6, the island’s public television station. Watching one of my favorite sitcoms on what I then considered the boring channel was rather odd. However, I never thought it strange that the Peñas, ¿Qué pasa U.S.A.? ’s working-class three-generation Cuban/Cuban-American family, resided in Miami or that some of the characters communicated bilingually in English and Spanish. For me, ¿Qué pasa U.S.A.? was a show that resembled other locally produced situation comedies broadcast on commercial television, with the difference that the Peña family were Cuban immigrants who, instead of residing in Puerto Rico (like some of my childhood friends), lived in Miami (like many of my friends’ relatives). Probably as a result of the principal characters’ cultural references and their accents in Spanish, I decoded ¿Qué pasa U.S.A.? as a Cuban sitcom. Fast-forward to 2004. I was invited to write a 500-word encyclopedia entry on ¿Qué pasa U.S.A.? Without having any information on the show at hand, I immediately accepted. This was an opportunity to revisit a program I loved. After conducting the research I realized the uniqueness of ¿Qué pasa U.S.A.? Sponsored by the U.S. Ofﬁce of Education Emergency School Assistance Act– Television Program (ESAA-TV), ¿Qué pasa U.S.A.? —considered the ﬁrst bilingual situation comedy broadcast on U.S. television— addressed the culturalgenerational misunderstandings and the socio-cultural adjustments endured by the Peñas, a 1960 Cuban exile family.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Cuba (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Planet TV: A Global Television Reader - Parks, Lisa; Kumar, Shanti (NYU Press, 2003)
From the 1967 live satellite program "Our World" to MTV music videos in Indonesia, from French television in Senegal to the global syndication of African American sitcoms, and from representations of terrorism on German television to the international Teletubbies phenomenon, TV lies at the nexus of globalization and transnational culture. Planet TV provides an overview of the rapidly changing landscape of global television, combining previously published essays by pioneers of the study of television with new work by cutting-edge television scholars who refine and extend intellectual debates in the field. Organized thematically, the volume explores such issues as cultural imperialism, nationalism, postcolonialism, transnationalism, ethnicity and cultural hybridity. These themes are illuminated by concrete examples and case studies derived from empirical work on global television industries, programs, and audiences in diverse social, historical, and cultural contexts. Developing a new critical framework for exploring the political, economic, sociological and technological dimensions of television cultures, and countering the assumption that global television is merely a result of the current dominance of the West in world affairs, Planet TV demonstrates that the global dimensions of television were imagined into existence very early on in its contentious history. Parks and Kumar have assembled the critical moments in television's past in order to understand its present and future. Contributors include Ien Ang, Arjun Appadurai, Jose B. Capino, Michael Curtin, Jo Ellen Fair, John Fiske, Faye Ginsburg, R. Harindranath, Timothy Havens, Edward S. Herman, Michele Hilmes, Olaf Hoerschelmann, Shanti Kumar, Moya Luckett, Robert McChesney, Divya C. McMillin, Nicholas Mirzoeff, David Morley, Hamid Naficy, Lisa Parks, James Schwoch, John Sinclair, R. Anderson Sutton, Serra Tinic, John Tomlinson, and Mimi White.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé